Analisis Hasil Commissioning Test Transformator Distribusi 100 kVA pada Rumah Sakit As Syifa - Hadinata, Angga Pratama; Nrartha, I Made Ari; Nababan, Sabar (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING, INFORMATION TECHNOLOGY, CONTROL ENGINEERING, AND ROBOTIC), 2025)
Commissioning test on a distribution transformer is a series of tests conducted to ensure that the distribution transformer functions properly and meets the specifications before it is put into operation. This testing is crucial to verify that the transformer is ready for use in the electrical distribution system and to prevent potential issues or failures in the future. The commissioning test includes measuring insulation resistance, ground resistance, and phase-to-phase and phase-to-neutral voltages. The instruments used for these measurements are an insulation tester, earth tester, and clamp meter. The measurement results in this study are all in accordance with PLN standards. The insulation resistance measurements for phases R, S, and T are 2.99 GΩ, 2.34 GΩ, and 2.54 GΩ, respectively. For grounding resistance, the measurements for the neutral of the main distribution panel (PHB), transformer body, and lightning arrester are 2.72 Ω, 3.32 Ω, and 2.87 Ω, respectively. In the phase-to-phase voltage measurements, the values for phases R-S, R-T, and S-T are 406 V, 405 V, and 407 V, respectively. In the phase-to-neutral voltage measurements, the values for phases R, S, and T are 232 V, 233 V, and 233 V.